An Exploratory Study of Mergers and Acquisitions by Looking at an Entrepreneurial Firm - He, Zhen (2012)
Substantial previous research has studied different issues associated with merger and acquisition (M&A) activities due to its increasing popularity and importance in the global economy. However, very little of the empirical studies have been done into the field related to entrepreneurial firms’ M&A events and it is seen as more complicated than typical firms. In response, this study investigates the problems entrepreneurial firms encounter during M&A activities using a case study of an acquisition between two entrepreneurial firms to cover this gap. The results suggest that entrepreneurial firms cannot avoid some similar problems related to culture, HRM, leadership, trust, organizational re-structuring and knowledge transfer as other administrative companies. Whereas, the findings reveal that it might be easier for entrepreneurial corporations to overcome the problems in the post-acquisition integration, due to the impact of entrepreneurial culture, though some unique problems occur particularly for these types of companies, such as an organizational members’ inability to cope with the sudden growth, difficulties resulted from entrepreneurs’ over-optimism and over-confidence.